A mobile application for UiTM bus scheduling system / Nur Anis Izzati Anuar - Anuar, Nur Anis Izzati (2020)
The Bus Scheduling System is an integrated electronic management system. This system ensures that the management process can be done smoothly. This system will also help reduce the faults caused by human faults. This system was developed as one of the solutions to switch from current manual practices to more systematic computerized systems. This final year project proposes a mobile phone application that provides information on buses, bus numbers and even online and offline bus routes.